The determination of specificity, sensitivity and accuracy of core needle biopsy in the diagnosis of parotid and submandibular salivary glands tumors - Oroz Aleksandar; Bokun Zorana; Antonijević Đorđe; Jevđić Jasna (Vojnosanitetski Pregled)
Background/Aim. The diagnosis of tumors of salivary glands relies heavily on radiological examination and biopsy of pathological tissue. The aim of this study was to investigate the sensitivity, specificity and accuracy of core needle biopsy in diagnosis of tumors of parotid and submandibular glands. Methods. This study was designed as a crosssectional clinical trial performed between May 2008 and Мay 2015 at the Department of Otorhinolaryngology and Maxillofacial Surgery, Clinical Center Zemun, Belgrade, Serbia. The examinations included 200 patients among which 100 were diagnosed with tumors of parotid salivary glands and 100 with tumors of submandibular salivary glands. The core needle biopsy was undertaken in all cases where tumor was smaller than 2 cm, far from blood vessels and far from the deep layer of parotid gland. The histopathological analysis was performed to identify histological type of the lesion. Upon performing the surgical procedure and consequently the tumor tissue extirpation, tissue samples obtained were investigated for the definitive diagnosis. Results. The sensitivity of the procedure was 90.9% for parotid salivary gland and 74% for submandibular salivary gland, the specificity was 95.9% for parotid salivary gland and 93% for submandibular salivary gland and the accuracy was 94.7% for parotid salivary gland and 87% for submandibular salivary gland. Based on the histopathological findings of the salivary glands obtained using core needle biopsy of the tumor tissue, it was possible to differentiate between malignant and benign lesions. Conclusion. Current investigation points to the advantages and efficiency of core needle biopsy in diagnosis of tumors of parotid and submandibular salivary glands.